Presentation of a Strategic Management Model for Industrial Cooperatives in the Country with a Future-Oriented Perspective - Foroutan , Mostafa; Zolfagharzadeh kermani, Mohamad Mahdi; Afshar Kazemi, Mohammad ali (Business, Marketing, and Finance Open, 2025)
The present study aimed to propose a strategic management model for industrial cooperatives in the country with a future-oriented perspective. The research method was based on structural equation modeling using a quantitative approach. The research population consisted of experts, scholars, specialists, and knowledgeable individuals. A sample size of 107 participants was selected using Cochran's formula. The research instrument was a researcher-made questionnaire. The collected data were analyzed using both descriptive and inferential statistical methods with SPSS 16 and Smart PLS software. The results indicated that seven components played a role in defining an appropriate framework for presenting a strategic management model for industrial cooperatives in the country with a future-oriented perspective. These components included bureaucracy or structural bureaucracy, organizational transparency, job segmentation and job classification in line with strategy implementation, job interweaving aligned with strategies, strategic cohesion and integration, financial resources with a future-oriented approach, and future-oriented educational resources. To assess the model fit, indices such as X², R, and R² were examined, where a low X² value, a chi-square to degrees of freedom ratio of less than three, and the calculated coefficient of determination and adjusted coefficient of determination indicated a good model fit.